Widespread recent ecosystem state shifts in high‐latitude peatlands of northeastern Canada and implications for carbon sequestration. (25th December 2021) - Magnan, Gabriel; Sanderson, Nicole K.; Piilo, Sanna; Pratte, Steve; Väliranta, Minna; van Bellen, Simon; Zhang, Hui; Garneau, Michelle
Abstract: Northern peatlands are a major component of the global carbon (C) cycle. Widespread climate‐driven ecohydrological changes in these ecosystems can have major consequences on their C sequestration function. Here, we synthesize plant macrofossil data from 33 surficial peat cores from different ecoclimatic regions, with high‐resolution chronologies. The main objectives were to document recent ecosystem state shifts and explore their impact on C sequestration in high‐latitude undisturbed peatlands of northeastern Canada. Our synthesis shows widespread recent ecosystem shifts in peatlands, such as transitions from oligotrophic fens to bogs and Sphagnum expansion, coinciding with climate warming which has also influenced C accumulation during the last 100 years. The rapid shifts towards drier bog communities and an expansion of Sphagnum sect. Acutifolia after 1980 CE were most pronounced in the northern subarctic sites and are concurrent with summer warming in northeastern Canada. These results provide further evidence of a northward migration of Sphagnum ‐dominated peatlands in North America in response to climate change. The results also highlight differences in the timing of ecosystem shifts among peatlands and regions, reflecting internal peatland dynamics and varying responses of vegetation communities. Our study suggests that the recent rapid climate‐driven shifts from oligotrophic fen to drier bog communities have promoted plant productivity and thus peat C accumulation. We highlight the importance of considering recent ecohydrological trajectories when modelling the potential contribution of peatlands to climate change. Our study suggests that, contrary to expectations, peat C sequestration could be promoted in high‐latitude non‐permafrost peatlands where wet sedge fens may transition to drier Sphagnum bog communities due to warmer and longer growing seasons. Abstract : This synthesis of plant macrofossil data from 33 surficial peat cores shows widespread recent ecosystem shifts in peatlands of northeastern Canada. The data show evidence of extensive transitions from oligotrophic fens to bogs, Sphagnum expansion and surface drying coinciding with documented climate warming during the 20th century. The shift towards drier bog plant communities and increases in Sphagnum abundance was the most pronounced in the northernmost subarctic sites. Our study suggests that these recent ecosystem shifts have promoted plant productivity and peat C accumulation.